Prevalence, awareness, treatment and control of hypertension in the adult Polish population – Multi-center National Population Health Examination Surveys – WOBASZ studies - Arkadiusz Niklas; Anna Flotyńska; Aleksandra Puch-Walczak; Maria Polakowska; Roman Topór-Madry; Maciej Polak; Walerian Piotrowski; Magdalena Kwaśniewska; Paweł Nadrowski; Andrzej Pająk; Wojciech Bielecki; Krystyna Kozakiewicz; et al. (Archives of Medical Science, 2018)
Introduction : Hypertension is one of the main risk factors of cardiovascular diseases. The first aim of the study was to evaluate the prevalence, awareness and treatment of hypertension as well as treatment effectiveness (blood pressure < 140/90 mm Hg) in a representative sample of the Polish population over the age of 19, examined in the WOBASZ II program. The second aim was to assess the changes in these parameters between 2003–2005 (WOBASZ study) and 2013–2014 in adults aged 20–74. Material and methods : Sampling was performed in three stages, stratified according to voivodeship (province), type of commune, and gender. Finally, the study included 6163 persons (3406 women and 2757 men) examined in the years 2013–2014 (aged ≥ 19 years). For comparison the data from 14 755 persons (7783 women and 6452 men aged 20–74 years) examined in the years 2003–2005 were used. Results : In the years 2013–2014, the age-standardized prevalence of hypertension, awareness, treatment and control was 42.7%, 59.3%, 46.1%, and 23% respectively. In the last decade an increase in the prevalence of hypertension (relative ratio (RR) 1.12; 95% confidence interval (CI): 1.07–1.18), treatment (RR = 1.26; 95% CI: 1.17–1.36) and control (RR = 2.16; 95% CI: 1.91 2.45) was found. In contrast, the awareness decreased nonsignificantly (RR = 0.98; 95% CI: 0.92–1.05). Conclusions : The prevalence of hypertension in Poland is high, and increased by about 12% in 10 years. Although the number of treated patients and blood pressure control improved nearly twofold over the last decade, this is still below expectations. Efforts to improve the diagnosis and effective treatment of hypertension in Poland should still be intensified.